Economic and economic-statistical designs of variable sample size and sampling interval coefficient of variation chart - Chew, Y. Y.; Khoo, B. C.; Khaw, K. W.; Yeong, W. C. * (John Wiley, 2020)
In the literature, the variable sample size and sampling interval (VSSI) coefficient of variation (CV) chart was shown to have a better statistical performance than the Shewhart (SH) CV chart which uses fixed sample size and sampling interval. The VSSI CV chart adopts more frequent sampling and larger sample size when the process quality deteriorates for quicker detection of a process shift as there is a higher tendency for the said shift to occur. This paper investigates the economic and economic-statistical performances of the VSSI CV chart as the previous study only analyzes the chart’s statistical performance. By minimizing the cost via economic and economic-statistical designs, the VSSI CV chart can be implemented more economically. Statistical constraints are added in the economic-statistical design of the VSSI CV chart which makes it different from the economic design of the aforementioned chart. Numerical examples are given to illustrate the economic and economic-statistical performances of the VSSI CV chart, where a comparison with the SH CV chart is made. A study of misspecification of the shift size is also conducted to study the effect of wrongly specifying the shift size.